Recurrent Ovarian Cancer: The Role of Radiation Therapy. Issue 4 (1st May 2017) - De Felice, Francesca; Marchetti, Claudia; Di Mino, Andrea; Palaia, Innocenza; Benevento, Ilaria; Musella, Angela; Musio, Daniela; Tombolini, Vincenzo
Abstract : Objective: The aim of this review was to present the current radiation therapy status in recurrent ovarian cancer (OC) and explore potential solution to improve clinical outcomes in this setting of patients. Materials and Methods: PubMed search was performed. An attempt was made to include all relevant studies. Pertinent references cited in selected articles were also considered. Results: The role of radiation therapy in recurrent OC needs to be defined. This is the largest reported analysis of published data. Conclusions: Chemotherapy is the mainstay of recurrent OC treatment but prognosis remains very poor, and novel therapies are required to be integrated into this consolidated treatment regimen. Radiation therapy represents a valid alternative approach, even if no clear guidelines are available concerning it.